2018
DOI: 10.26434/chemrxiv.6890807.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bimolecular Reaction Dynamics in the Phenyl - Silane System: Exploring the Prototype of a Radical Substitution Mechanism

Abstract: We present a combined experimental and theoretical investigation of the bimolecular gas phase reaction of the phenyl radical (C6H5) with silane (SiH4) under single collision conditions to investigate the chemical dynamics of forming phenylsilane (C6H5SiH3) via a bimolecular radical substitution mechanism at a tetra-coordinated silicon atom. Verified by electronic structure and quasiclassical trajectory calculations, the replacement of a single carbon atom in methane by silicon lowers the barrier to substitutio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…23 Disilene (Si 2 H 4 ) exists as a trans-bent molecule with sp 3 hybridized silicon atoms, but the ethylene (C 2 H 4 ) molecule is planar with both carbon atoms sp 2 hybridized. 24,25 However, whereas an understanding of the chemistry of silane (SiH 4 ) with carbon-bearing reactants in CSEs is beginning to emerge, 22,26,27 the chemistry of disilane (Si 2 H 6 ) has remained largely unexplored. An elucidation of the reaction dynamics of disilane (Si 2 H 6 ) with ground-state atomic carbon (C( 3 P j )) as the simplest "organic" open shell species affords an exceptional opportunity to gauge the activation of disilane through the initial formation of silicon−carbon versus silicon− hydrogen bonds under single collision conditions.…”
Section: Introductionmentioning
confidence: 99%
“…23 Disilene (Si 2 H 4 ) exists as a trans-bent molecule with sp 3 hybridized silicon atoms, but the ethylene (C 2 H 4 ) molecule is planar with both carbon atoms sp 2 hybridized. 24,25 However, whereas an understanding of the chemistry of silane (SiH 4 ) with carbon-bearing reactants in CSEs is beginning to emerge, 22,26,27 the chemistry of disilane (Si 2 H 6 ) has remained largely unexplored. An elucidation of the reaction dynamics of disilane (Si 2 H 6 ) with ground-state atomic carbon (C( 3 P j )) as the simplest "organic" open shell species affords an exceptional opportunity to gauge the activation of disilane through the initial formation of silicon−carbon versus silicon− hydrogen bonds under single collision conditions.…”
Section: Introductionmentioning
confidence: 99%
“…15 Although both the nucleophilic (S N ) and electrophilic (S E ) substitution mechanisms have aided in unraveling the physical organic mechanistic framework driving molecular mass growth processes through carbon−carbon bond coupling, the unraveling of dynamics of radical (S R ) substitution reactions in gas phase, also referred to as homolytic radical substitution reactions, of reactants carrying tetracoordinated carbon or isovalent silicon atoms has been sparse predominantly due to the experimental difficulties in preparing the radical reactants in sufficient concentrations to allow the detection of the nascent reaction products. 16 In pioneering studies, detailed reactive collision mechanisms were revealed through the simplest hydrogen-atom exchange reaction of atomic hydrogen (H) with molecular hydrogen (H 2 ); 17,18 Dixon et al 19 along with Zare et al, 20 Truhlar et al, 21 and Zhao et al 13 unraveled the underlying mechanisms of the reaction of atomic hydrogen (H) with methane (CH 4 ) or D4-methane (CD 4 ). A direct hydrogen abstraction pathway forming molecular hydrogen along with the methyl radical (CH 3 ) was exposed to a barrier of 63 kJ mol −1 , which was energetically preferred to the radical substitution channel leading to methane (CH 4 ) and H with a 159 kJ mol −1 barrier.…”
Section: Introductionmentioning
confidence: 99%